A new species, Procloeon monilistylus sp. n. (Ephemeroptera, Baetidae), from the Russian Far East - Kluge, Nikita J.; Tiunova, Tatiana M.; Novikova, Eugenia A. (Zootaxa, 2014)
A new, two-winged species Procloeon monilistylus sp. n. is described from the Russian Far East based on male and female imagoes reared from larvae. The larva differs from other species of Procloeon by having a deeply separated incisor and kinetodontium of the mandibles. The imago differs from all Baetidae (and mayflies in general) by the shape of the gonostyli. Formerly this species was known as "Cloeon (Centroptilum) sp. 1" sensu Kluge & Novikova 1992.